PENGARUH KONSUMSI KAFEIN PADA KOPI TERHADAP KUALITAS TIDUR MAHASISWA FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Ardianti Putri (FKU 15 UMY 581, 2015)
Caffeine is a psychoactive most commonly consumed in the community. Intake of caffeine occurs from ingestine coffee, tea, chocolate and others. Its pharmacological effects are predominantly due to its function as antagonist of adenosine receptor which can alter the function of central nervous system and can interfere with sleep quality. Sleep quality includes both quantitative and qualitative aspects of sleep. The purpose of this study is to determine the effect of caffeine on sleep quality in student of Faculty Medicine Muhammadiyah University Yogyakarta. This study is an analitic observasional with a crossectional desain. The sample in this study were students who are willing and meet the inclusion criteria, selected with simple random sampling. 40 subjects were divided into two different group, those who consumed coffee (20 people) and who not consumed coffee (20 people). Their quality of sleep was then measured using Sleep Quality Questionnaire. The data was analyzed using Spearman hypothesis test. The result shows that 2,5 % who consumed coffee with good quality of sleep , 47,5% who consumed coffee with bad quality of sleep, 20% who not consumed coffee with good quality of sleep, and 30% who not consumed coffee with bad quality of sleep. Totally 22,5% who have exprerience good quality of sleep and 77,5% who have experience bad quality of sleep. Thus, the end results of the hypothesis test shows that there are relation between consumed coffee with quality of sleep (p=0,005). It is recommended to public, especially students to decrease the usage of caffeine, especially at night cause its proven to worsen the quality of sleep. Caffeine reduces hours of sleep, prolonged sleep onset, reduce sleep satisfaction and can cause weakness in the morning